Prevalence of Serum Celiac Antibodies in a Multiracial Asian Population-A First Study in the Young Asian Adult Population of Malaysia - Theresa Wan-Chen Yap; Weng-Kai Chan; Alex Hwong-Ruey Leow; Ahmad Najib Azmi; Mun-Fai Loke; Jamuna Vadivelu; Khean-Lee Goh (Public Library of Science, 2024)
Background: Celiac disease (CD) is an immune-mediated disorder induced by the ingestion of gluten in genetically susceptible persons. The prevalence of CD in Malaysia is unknown. We aim to determine the seroprevalence of CD antibodies and also investigate the correlation between H. pylori infection and CD in the young and healthy multiracial Malaysian population. Methods: Healthy young adult volunteers between the ages of 1830 years were consecutively recruited from June 2012 to May 2014 at the University of Malaya Medical Centre (UMMC), Kuala Lumpur. Serum samples from all the participants were tested for anti-gliadin antibody immunoglobulin A/immunoglobulin G (IgA/IgG) and anti-tissue transglutaminase antibody (tTG) IgA/IgG. Samples positive for both anti-gliadin and anti-tTG were further validated for anti-human endomysial IgA antibodies (EmA). Serological diagnosis of CD was made when anti-gliadin, anti-tTG and anti-EmA were positive. Conclusions: The seroprevalence of CD antibodies in healthy young adults in the Malaysian population was 1.25% (1 in 100). CD is underdiagnosed and it could be a much greater problem in Malaysia than previously thought.